PM2.5 Emission Elemental Composition from Diverse Combustion Sources in the Metropolitan Area of Mexico City - V. Mugica; F. Mugica; M. Torres; J. Figueroa (The Scientific World Journal)
A field study was carried out from 2003 to 2004 with the aim to develop the PM2.5 emission source profiles from light-duty gasoline and heavy-duty diesel vehicles, as well as emission source profiles from waste incineration, wood burning, LP gas combustion, and meat broiling. Over 25 chemical species were quantified from the fine particles emitted by the different combustion sources investigated, including organic and elemental carbon, ions, and elements. The OC/TC ratio found in the different PM2.5 profiles was dissimilar as well as the sulfate, nitrate, ammonium, soil species, and trace element content. Consequently, these combustion emission profiles could be used in source reconciliation studies for fine particles.